TINDAK TUTUR MEMINTA OLEH PEMBELAJAR BIPA DARI KOREA: KAJIAN PRAGMATIK BAHASA ANTARA (INTERLANGUAGE PRAGMATICS) - Adista Nur Primantari; I Dewa Putu Wijana (Universitas Muhammadiyah Surakarta, 2017)
This study is aimed at explaining what causes the differences occurred in Indonesianrequest utterances produced by Korean learners of Indonesian. The data used inthis research were taken directly from the fieldwork. The data were taken throughdirect observation by recording and taking notes from conversations between Koreanpeople living in Yogyakarta whostudies Indonesian language. To collect the data,the researcher distributed questionnaires. After collecting the data, the researcheranalyzed them in the area of pragmatics, compared the data between the Koreanand Indonesian speakers, and discussed the factors causing the differences. Theresearcher reveals that the Korean learning Indonesian produce different requestutterance forms compared to the native speakers. The factors of request utterancedifferences used by Korean learning Indonesian are mainly caused by linguistics andnon-linguistics factors. The linguistics factors are the impact of Korean pragmaticsknowledge transfer and the imperfection of grammatical knowledge meanwhile thenon-linguistics factors are cultural differences, intake of Indonesian learning, andhabit of using informal forms in daily conversation.